2000
DOI: 10.1021/bi002080p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Active-Site Residues of the Pro-Metastatic Endoglycosidase Heparanase

Abstract: Heparanase is a beta-D-endoglucuronidase that cleaves heparan sulfate (HS) and has been implicated in many important physiological and pathological processes, including tumor cell metastasis, angiogenesis, and leukocyte migration. We report herein the identification of active-site residues of human heparanase. Using PSI-BLAST and PHI-BLAST searches of sequence databases, similarities were identified between heparanase and members of several of the glycosyl hydrolase families (10, 39, and 51) from glycosyl hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 52 publications
(85 reference statements)
11
148
0
Order By: Relevance
“…This study identified heparanase a binding mode of aspirin that was beyond heparin-binding sites. We have shown that Lys159 and Glu225 of heparanase are critical for aspirin binding, consistent with previous findings that Glu225 and Glu343 are key residuals essential for the activity of heparanase (46,47). Hence, we proposed a mechanism for aspirin that inhibiting the activity of heparanase by binding to Glu150 (Q9Y251: Glu 225), similar to two types of small-molecular inhibitors (48,49).…”
Section: Discussionsupporting
confidence: 89%
“…This study identified heparanase a binding mode of aspirin that was beyond heparin-binding sites. We have shown that Lys159 and Glu225 of heparanase are critical for aspirin binding, consistent with previous findings that Glu225 and Glu343 are key residuals essential for the activity of heparanase (46,47). Hence, we proposed a mechanism for aspirin that inhibiting the activity of heparanase by binding to Glu150 (Q9Y251: Glu 225), similar to two types of small-molecular inhibitors (48,49).…”
Section: Discussionsupporting
confidence: 89%
“…The three-dimensional structure of heparanase is not yet known in detail. Translation of the primary structure of heparanase over another endo-␤-glycosidase (␤-xylanase) shows clusters of basic amino acid residues at least one of which is conceivably implicated in binding to sulfate groups of the substrate (55). Our preliminary studies, applying point mutations and deletions as well as synthetic peptides, identified amino acid residues 158 -171 as the predominant HS binding domain of the heparanase molecule.…”
Section: Discussionmentioning
confidence: 82%
“…1A) suggests that the N terminus of the 50 kDa protein undergoes conformational changes upon heparanase processing, exposing an epitope that is not present in the 65 kDa heparanase precursor. Although this region is not considered to be part of the heparanase active site (Hulett et al, 2000), it may well be involved in a three-dimensional organization assumed by the 50 kDa heparanase upon processing, and that is necessary for enzymatic activity. To test this hypothesis, recombinant purified heparanase was incubated with affinity-purified antibody 733 or control rabbit IgG, and enzymatic activity was determined.…”
Section: Antibody 733 Inhibits Heparanase Enzymatic Activitymentioning
confidence: 99%